Antinociceptive Activity of Chemical Components of Essential Oils That Involves Docking Studies: A Review - Assis, Davidson Barbosa; Aragão Neto, Humberto de Carvalho; da Fonsêca, Diogo Vilar; de Andrade, Humberto Hugo Nunes; Braga, Renan Marinho; Badr, Nader; Maia, Mayara dos Santos; Castro, Ricardo Dias; Scotti, Luciana; Scotti, Marcus Tullius; de Almeida, Reinaldo Nóbrega (Frontiers in Pharmacology, 2020)
Pain is considered an unpleasant sensory and emotional experience, being considered as one of the most important causes of human suffering. Computational chemistry associated with bioinformatics has stood out in the process of developing new drugs, through natural products, to manage this condition. Objective: To analyze, through literature data, recent molecular coupling studies on the antinociceptive activity of essential oils and monoterpenes. Data source: Systematic search of the literature considering the years of publications between 2005 to December 2019, in the electronic databases PubMed and Science Direct. Eligibility criteria: Were considered as criteria of 1) Biological activity: non-clinical effects of an OE and / or monoterpenes on antinociceptive activity based on animal models and in silico analysis, 2) Studies with plant material: chemically characterized essential oils and / or their constituents isolated, 3) clinical and non-clinical studies with in silico analysis to assess antinociceptive activity, 4) articles published in English. Exclusion criteria were literature review, report or case series, meta-analysis, theses, dissertations and book chapter. Results: Out of 16006 articles, 16 articles fulfilled all the criteria. All selected studies were non-clinical. The most prominent plant families used were Asteraceae, Euphorbiaceae, Verbenaceae, Lamiaceae and Lauraceae. Among the phytochemicals studied were α-Terpineol, 3-(5-substituted-1,3,4-oxadiazol-2-yl)-N'-[2-oxo-1,2-dihydro-3H-indol-3-ylidene] propane hydrazide, β-cyclodextrin complexed with citronellal, (-)-α-bisabolol, β-cyclodextrin complexed with farnesol and p-Cymene. The softwares used for docking studies were Molegro Virtual Docker, Sybyl®X, Vlife MDS, AutoDock Vina, Hex Protein Docking and AutoDock 4.2 in PyRx 0.9. The molecular targets/complexes used were Nitric Oxide Synthase, COX-2, GluR2-S1S2, TRPV1, β-CD complex, CaV1, CaV2.1, CaV2.2, and CaV2.3, 5-HT receptor, Delta receptor, Kappa receptor, and MU (μ) Receptor, Alpha Adrenergic, Opioid and Serotonergic receptors, Muscarinic receptors and GABAA Opioid and Serotonin receptors, 5-HT3 and M2 receptors. Many of the covered studies used molecular coupling to investigate the mechanism of action of various compounds, as well as molecular dynamics to investigate the stability of protein-ligand complexes. Conclusions: The studies revealed that through the advancement of more robust computational techniques that complement the experimental studies, they may allow some notes on the identification of a new candidate molecule for therapeutic use.